Long noncoding RNAs and viral infection: promising molecular markers? - Yu, Meng-Yao; Zhang, Jie-Xin; Wang, Fang (Journal of Laboratory and Precision Medicine, 2017)
Studies both in vitro and in vivo suggest that long noncoding RNAs (lncRNAs) are markers of viral infection. lncRNA expression patterns change when host cells are infected with a virus. Conversely, viral lncRNAs also regulate the gene expression of host cells, facilitating the replication of the virus itself and its escape from immune surveillance. Combined with clinical detection methods, lncRNAs are potential clinical biomarkers and may help in the diagnosis of virus-related diseases.